O desenvolvimento econômico e as Nações Unidas: uma análise da atuação do PNUD no Brasil - Machado, João Guilherme Rocha (2007)
The aim of this study is to assess the task performed by the United Nations Development Programme (UNDP), the United Nations main body for development issues, in Brazil. The method of research consists of bibliographical research, followed by a case study, in order to strengthen the theme s empirical investigation. The case study analyzed is the project BNDES/PNUD for Local Development (BRA/00/031) in the Península de Itapagipe , Salvador, Bahia. The first conclusion of this work is that the choice of the capabilities approach, developed by Amartya Sen, is convenient for the pragmatic and consensual nature of the Programme, given that it proposes a stronger focus on the expansion of individual choices without questioning the current international economic order. Therefore, it allows the maintenance of the support of not only countries which act as core resource suppliers, but also of countries where UNDP implements its interventions. Furthermore, the sustainable human development is a concept broad enough to let different interventions be classified under this one paradigm. Regarding the specific role of the UNDP in Brazil, it is clear that the nature of its approach is the government cost-sharing/national execution. This modality was first employed in a particular context, under special circumstances, which took under consideration the interests of both Brazilian government and the UNDP. It is possible to reach the conclusion that the Programme´s action in Brazil is more linked to performing the duties of a support structure, in order to have the projects fully and effectively implemented, than to furnish content and theoretical aspects to the interventions supported by the Programme. In sum, the UNDP´s action is limited by the lack of success in translating its innovative theoretical concepts and ideas into practical projects. Being successful on this task could imply an enrichment of the projects and also create a clear framework which characterizes the projects supported by the UNDP